Externalities of national pharmaceutical policy when markets are integrated through parallel trade - Laura Birg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper studies externalities of nationally determined cost-sharing systems, in particular coinsurance rates (patients pay a percentage of the price), under pharmaceutical parallel trade, i.e. trade outside the manufacturer's authorized distribution channel, in a two-country model with a vertical distributor relationship. Parallel trade generates a price-decreasing competition effect in the destination country and a price-increasing double marginalization effect in the source country. An increase of the coinsurance rates in the destination country of the parallel import mitigates the double marginalization effect in the source country. An increase of the coinsurance rate in the source country reinforces the competition effect in the destination country.
Keywords: F12; I11; I18; 330